Regressing basal-cell carcinoma masquerading as benign lichenoid keratosis - Aleksandra Kulberg; Wolfgang Weyers (Mattioli1885, 2016)
Background: Benign lichenoid keratosis (BLK, LPLK) is often misdiagnosed clinically as superficial basal-cell carcinoma (BCC), especially when occurring on the trunk. However, BCCs undergoing regression may be associated with a lichenoid interface dermatitis that may be misinterpreted as BLK in histopathologic sections. Methods: In order to assess the frequency of remnants of BCC in lesions interpreted as BLK, we performed step sections on 100 lesions from the trunk of male patients that had been diagnosed as BLK. Results: Deeper sections revealed remnants of superficial BCC in five and remnants of a melanocytic nevus in two specimens. In the original sections of cases in which a BCC showed up, crusts tended to be more common, whereas vacuolar changes at the dermo-epidermal junction and melanophages in the papillary dermis tended to be less common and less pronounced. Conclusions: Lesions from the trunk submitted as BCC and presenting histopathologically as a lichenoid interface dermatitis are not always BLKs. Although no confident recommendations can be given on the basis of this limited study, deeper sections may be warranted if lesions are crusted and/or associated with only minimal vacuolar changes at the dermo-epidermal junction and no or few melanophages in the papillary dermis.